2015
DOI: 10.3233/bme-151335
|View full text |Cite
|
Sign up to set email alerts
|

Golay improvement of the robustness of mean scatterer spacing measurement with ultrasonic backscattering

Abstract: Abstract. Mean scatterer spacing (MSS) estimated from ultrasonic backscattering is of valuable information for tissue characterization. However, low ultrasound frequency, sound attenuation, and diffuse scattering significantly disturb the current MSS measurement methods. The aim of this study is to improve MSS measurement with Coded Excitation (CE) enhanced cepstrum estimation. The study proposes a Golay code-based cepstrum estimation and uses an equivalent Faran cylinder model of cancellous bone. By solving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Pan et al incorporated coded excitation (Golay) into FT power cepstrum MSS estimate. 61 Benefits brought by coded excitation include longer penetration depth, suppression of interference peaks in power cepstrum estimation, and robustness against noise.…”
Section: Classification By Clinical Applicationmentioning
confidence: 99%
“…Pan et al incorporated coded excitation (Golay) into FT power cepstrum MSS estimate. 61 Benefits brought by coded excitation include longer penetration depth, suppression of interference peaks in power cepstrum estimation, and robustness against noise.…”
Section: Classification By Clinical Applicationmentioning
confidence: 99%
“…Since then, the publication rate of studies related to periodicity estimation has slowed down. Recently, Pan et al (2014Pan et al ( , 2015 presented a method of mode decomposition-based cepstrum spacing measurement of MSS changes in quasi-periodic trabecular bones. In 2013, Rubert and Varghese (2013) compared multitaper coherence and single-taper to estimate MSS and concluded that the multi-taper significantly improves over single-taper.…”
Section: Introductionmentioning
confidence: 99%
“…They used simulated and real backscattered echoes of liver tissues in vivo and concluded that their method is potentially superior to Simon's (1997), avoiding false peaks in the spectrum. More recently, Pan et al (2015) proposed a Golay code-based cepstrum estimation and the results show that the method is robust against noise.…”
Section: Introductionmentioning
confidence: 99%